Inflation Targeting for Turkey - Tasar, Izzet; Bayat, Tayfur (Elsevier Science Bv, 2015)
In this study, we analyze the behavior of inflation rate in Turkey by using monthly data belonging 2003:M01-2014:M08 period. We employ Markov Switching Auto regression (MSI-AR) approach in order to investigate whether the monetary authorities have asymmetric behaviors. Results imply that the Central Bank of the Republic of Turkey plays active or inactive role in the economy due to economic conditions. (C) 2015 Published by Elsevier B.V.
International Conference on Emerging Markets Queries in Finance and Business (EMQFB) -- OCT 24-25, 2014 -- Bucharest, ROMANIA
Keywords: Inflation Targeting; Consumer Price Index; Markow Switching VAR